FUNGSI SUBJEK DALAM KITAB KEJADIAN (SUATU ANALISIS SINTAKSIS) - DENGAH, SINTIA YULITA (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2018)
ABSTRACTThis research entitled ?the Function of Subject in the Book of Genesis? aims at identifying and classifying the functions subject and analyzing the realizations of functions subject.The method of this research is descriptive method. There are three steps to finish this research. First step is preparation, the writer reads the book of Genesis and several books that are related to this research. Second step is data collection, the writer collected the data from the book of Genesis then the writer identified and classified the functions subject according to the theory of Aarts and Aarts (1982). Third step the data were analyzed in terms of the realizations of functions subject, used the theory of Aarts and Aarts (1982).The results of this research shows that: first, there are four criteria of functions subject found in this book, those are Position (28 data), Concord (28 data), Passivization (4 data) and Repetition in tag-questions (1 data). Furthermore, there are six realizations of function subject found in this book, those are Noun Phrase (25 data), Finite Clause (4 data), Non-Finite Clause (3 data), Anticipatory It + Finite/Non-Finite Clause (1 data), Unstressed There (7 data) and Prepositional Phrase (5 data) found in the book of Genesis. Keywords: Function Subject; book of Genesis, Syntax; Aarts and Aarts.